2013
DOI: 10.1016/j.ajo.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Tomographic Features of Dome-Shaped Macula by Swept-Source Optical Coherence Tomography

Abstract: In highly myopic eyes with a dome-shaped macula, a horizontal ridge is formed within the posterior staphyloma by uneven thinning of the sclera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 40 publications
5
114
3
Order By: Relevance
“…Previous reports have reported non-specific pigmentary changes and yellow spots correlating to the area of FCE on fundal examination, but none reported the direct visualization of the excavation clinically. [1][2][3]5,8 Of our three patients with no co-existing pathology at the site of FCE, RPE mottling at the area of excavation was seen in two eyes, whereas no abnormality was detected in the remaining eye. In these eyes, observation over time did not show any worsening of symptoms or clinical appearance on fundal examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have reported non-specific pigmentary changes and yellow spots correlating to the area of FCE on fundal examination, but none reported the direct visualization of the excavation clinically. [1][2][3]5,8 Of our three patients with no co-existing pathology at the site of FCE, RPE mottling at the area of excavation was seen in two eyes, whereas no abnormality was detected in the remaining eye. In these eyes, observation over time did not show any worsening of symptoms or clinical appearance on fundal examination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating FCE in CSC patients, the site of FCE was also located in the area of angiographic leakage and choroidal hyperpermeability. 5 As FCE is largely thought to be a choroidal abnormality and the pathogenesis of PCV, CNV, and CSC are thought to be choroidal in nature, it has been suggested that FCE could predispose to the above conditions. 5 However, it remains unproven that FCE is a platform for such choroidal pathologies to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILM peeling is indicated when apparent ILM traction is recognized on OCT to prevent postoperative recurrence of MTM. 83 However, ILM peeling may increase the risk of postoperative full-thickness MH, because peeling may induce breaks within the already thinned and weakened central foveal tissue. 84 A fovea-sparing ILM peeling technique has been proposed, which enabled release of macular traction, reduced risk of surgical trauma to the central fovea, and centripetal contraction of the remaining ILM to prevent postop MH formation.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5] Although FCE was previously thought to have a congenital etiology, 2 recent evidence suggests that some cases of FCE are acquired. 5 To address whether the origin of FCE is congenital or acquired, investigating the presence of FCE in children is necessary because the choroid in children is relatively free from latent pathology that may contribute to the development of acquired FCE.…”
mentioning
confidence: 99%